An African West Nile virus risk map for travellers and clinicians. Issue 52 (March 2023) - García-Carrasco, José-María; Muñoz, Antonio-Román; Olivero, Jesús; Segura, Marina; Real, Raimundo
Abstract: International travellers are exposed to pathogens not commonly found in their countries of residence, including West Nile virus (WNV). Due to the difficulty of its diagnosis, little is known about its distribution in Africa. Understanding the geographic extent of risk of WNV infections is a necessity for both travellers and clinicians who advise and treat them, since there is no human vaccine. To date, there is no risk map for WNV infections in humans in Africa. Having a high-resolution risk map for the virus could be of relevance before the trip, to take preventive measures, and after the trip, for appropriate diagnosis of the disease. Virus detection in humans along the African continent were collected from official reports, and published scientific research for the period 1940 to 2020, and then geo-referenced in order to use biogeographical modelling for WNV. Models were based on fuzzy logic and machine learning algorithms and were designed to identify the environmental drivers that explain the distribution of human cases and to locate favourable areas for infections. We elaborated a high-resolution risk map for WNV infections that highlights favourable areas for infections in Africa. Although WNV infections are widely spread across Africa, the risk of the disease is not homogenously distributed. Popular tourist destinations such as Morocco, Tunisia, and South Africa, are high-risk areas for WNV infection. Highlights: The first risk map for human West Nile virus infection in Africa has been developed. High-risk areas have been detected where West Nile virus infection has not yet been detected. The highest risk areas coincide with major tourist destinations on the African continent. The risk map could help clinicians to advice departing travellers and properly diagnose travellers returning from Africa.